PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN SUASANA KERJA TERHADAP KINERJA GURU - Eka Saputra; Sudarwan Danim (Manajer Pendididikan, 2020)
This research aimed at analyzing the effect of leadership style and work atmosphere to the teacher's performance in Public Senior High School State in Bengkulu Tengah Regency. Leadership styles include: autocratic leadership styles, democratic leadership styles, and free leadership styles. Data collection was done using questionnaire. Data were analyzed using multiple linear regression analysis. Prerequisite test used is normality test, linearity test, multicolinearity, and independent test. The results showed that: (1) the autocratic leadership style has no effect to the teacher’s performance with significance test result of 0,05; (2) democratic leadership styles significant impact to the teacher’s performance; (3) free leadership style does not affect to the teacher’s performance; (4) work atmosphere significant impact to the teacher’s performance.